2011
DOI: 10.1055/s-0030-1255804
|View full text |Cite
|
Sign up to set email alerts
|

Cladosporium macrocarpumbrain abscess after endoscopic ultrasound-guided celiac plexus block

Abstract: A 45-year-old man presented with a 24-hour history of holocranial headache and right-side deviation of the oral commissure. He denied fever and other neurological symptoms. He had undergone endoscopic ultrasound (EUS)-guided celiac plexus neurolysis (CPN) 3 weeks before for the management of refractary epigastric pain caused by alcoholic chronic pancreatitis. On physical examination, cachexia (due to exocrine pancreatic insufficiency) was evident (body mass index of 16 kg/m 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…Case reports have shown a favorable outcome using azole-based therapies. ITC has shown efficacy in the treatment of superficial infections caused by C. cladosporioides, C. sphaerospermum, and C. oxysporum (8,14,37,(41)(42)(43)(44), while VRC was effective against C. macrocarpum in a brain abscess (17). This agrees with our in vitro data, which demonstrated that the azoles, particularly ITC and PSC, have good activity against Cladosporium species, although VRC displayed variable activity.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Case reports have shown a favorable outcome using azole-based therapies. ITC has shown efficacy in the treatment of superficial infections caused by C. cladosporioides, C. sphaerospermum, and C. oxysporum (8,14,37,(41)(42)(43)(44), while VRC was effective against C. macrocarpum in a brain abscess (17). This agrees with our in vitro data, which demonstrated that the azoles, particularly ITC and PSC, have good activity against Cladosporium species, although VRC displayed variable activity.…”
Section: Discussionsupporting
confidence: 87%
“…In the case of the C. herbarum complex, 13 of the 14 isolates morphologically identified as C. herbarum, also considered a clinically relevant species, were found to belong to other species of this complex (i.e., C. allicinum, C. macrocarpum, and C. ramotenellum). While C. macrocarpum has been identified as the causative agent of human infections (17), C. allicinum and C. ramotenellum have never been reported before in the clinical setting, although some isolates have been recorded as obtained from human samples (1). However, due to the lack of clinical histories and histopathological findings, it was impossible for us to confirm a pathogenic role of the species reported here for the first time from clinical specimens.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We identified at least two organisms in patients, E. rostratum and A. fumigatus, that caused infection. Additional fungi, most of which are common environmental molds but rarely cause human disease, [27][28][29][30][31][32][33] were identified in specimens from case patients, as well as in the product, 21 but are of unclear clinical significance. Some of these organisms, when injected into a sterile site, might have contributed to the disease by causing inflammatory reactions without true infection.…”
mentioning
confidence: 99%